2021
DOI: 10.3390/cancers13153827
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Clinical Application of Extracellular Vesicle-Derived DNA

Abstract: Extracellular vesicles (EVs) carry RNA, proteins, lipids, and diverse biomolecules for intercellular communication. Recent studies have reported that EVs contain double-stranded DNA (dsDNA) and oncogenic mutant DNA. The advantage of EV-derived DNA (EV DNA) over cell-free DNA (cfDNA) is the stability achieved through the encapsulation in the lipid bilayer of EVs, which protects EV DNA from degradation by external factors. The existence of DNA and its stability make EVs a useful source of biomarkers. However, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 161 publications
(244 reference statements)
0
24
0
Order By: Relevance
“…The most promising application of EVs genomics is its biomarker use, as EVs DNA reflects the mutational status of parental cells, making the diagnosis and prognosis of different pathological conditions, such as tumors, easier and more accessible. This is supported also by the enhanced availability of EVs DNA in body fluids as protected from degradation by the EVs lipid bilayer [ 102 ]. Many examples are given by the extensive research on liquid biopsies of various cancers [ 103 ]; for instance, Takur et al reported the detection of specific colon carcinoma-associated mutations in plasma-derived EV-DNA; Lee et al tested the sensitivity in detecting epidermal growth factor receptor (EGFR) mutations in EVs-DNA from BALF of patients with advanced non-small cell lung cancer (NSCLC) by targeted next-generation sequencing (NGS) of both tissue DNA and vesicular DNA [ 104 ].…”
Section: Extracellular Vesicle As Resourceful Biological Systemsmentioning
confidence: 99%
“…The most promising application of EVs genomics is its biomarker use, as EVs DNA reflects the mutational status of parental cells, making the diagnosis and prognosis of different pathological conditions, such as tumors, easier and more accessible. This is supported also by the enhanced availability of EVs DNA in body fluids as protected from degradation by the EVs lipid bilayer [ 102 ]. Many examples are given by the extensive research on liquid biopsies of various cancers [ 103 ]; for instance, Takur et al reported the detection of specific colon carcinoma-associated mutations in plasma-derived EV-DNA; Lee et al tested the sensitivity in detecting epidermal growth factor receptor (EGFR) mutations in EVs-DNA from BALF of patients with advanced non-small cell lung cancer (NSCLC) by targeted next-generation sequencing (NGS) of both tissue DNA and vesicular DNA [ 104 ].…”
Section: Extracellular Vesicle As Resourceful Biological Systemsmentioning
confidence: 99%
“…Exosomes can enter the recipient cell through receptor-ligand interactions ( Isaac et al, 2021 ; Staubach et al, 2021 ). Besides, exosomes can also be endocytosed by the recipient cells through phagocytosis ( Chen et al, 2021c ; Hur and Lee, 2021 ). Exosomes have an important role in tumor development and can serve as potential diagnostic markers and therapeutic targets for many tumors.…”
Section: Detection Of Exosomesmentioning
confidence: 99%
“…Other possible EV cargos such as DNA or lipids have not been evaluated yet in MM. While circulating cell-free DNA could serve as a possible biomarker, the presence of double stranded DNA inside small EVs remains controversial, which can be attributed to discrepancies in the preparation method and size of the isolated EVs 107 . Lipids are important players in a variety of processes including membrane formation and intracellular signaling.…”
Section: Exosome Biomarkersmentioning
confidence: 99%